Analysis The Quality of Website Service Information System Academic Integrated ( SIATER ) Bandar Lampung University Using Pieces Methods - Yusinta Ria Disanda (International Conference on Engineering and Technology Development (ICETD), 2014)
The use of information systems based on websites growing especially in providing facilities educational world to get some information that can be accessed online or connected to the internet. Of this research, the quality of websites academic integrated information system ( siater.ubl.ac.id ) measured by using the method pieces. Method pieces is engineering analysis method is used by j.lwhitten, l.dbentley, and k.cdittman in book called “system analysis method, 2004” is having 6 variable ( performance, information, economis, control,efficiency, service).From the analysis result and results questionnaire distributed to 317 respondents then can be concluded that website information system academic integrated ( siater.ubl.ac.id ) has met aspects existing on method pieces.But of its a low value to some questions, management website advised to give information more detailed and understandable.